Rancang Bangun Aplikasi untuk Menentukan Jalur Terpendek Menggunakan Algoritma Floyd di Lokasi Wisata Purbalingga - Irfan Ardiansyah; Dimara Kusuma Hakim (JUITA : Jurnal Informatika, 2012)
Purbalingga tourism are scattered in various locations complicate for local or foreign tourist in determining the path to go to tourist sites. By determining the starting point of shortest path from the town square of Purbalingga, the shortest path can be searched using Floyd algorithm. The workings of this algorithm are to find the possible paths exist by aggregating and comparing the points with positive weights on the path which has constructed and determined. The result of this research was obtained the shortest path to go to the various tourist sites in Purbalingga